Anatomy of the Southern African Boerhavia and Commicarpus species (Nyctaginaceae) - Struwig, Madeleen; Jordaan, Anine; Siebert, Stefan J. (Bangladesh Journal of Plant Taxonomy, 2011)
The Nyctaginaceae in southern Africa is represented by five genera of which Boerhavia L. and Commicarpus Standl. are the most species-rich. Stem, leaf and anthocarp material was collected in situ and examined with a scanning electron microscope and a light microscope. The anatomy of the leaf and anthocarp proved diagnostic at the generic level, but was uniform amongst the species of each genus. Kranz anatomy occurs around the minor veins in the leaves of Boerhavia, but in Commicarpus the minor veins are surrounded by large parenchyma cells. The anthocarp of Boerhavia has five ribs or three wings, with sclerenchyma within the ribs and the area between the ribs, whereas Commicarpus has ten ribs with sclerenchyma only present within the ribs. The number of chlorenchyma rows in the stems could be diagnostic and the outline of the sclerenchyma bundles in the anthocarp could divide the Commicarpus species into two groups, but more research needs to be done on these characters. Keywords: Stem; Leaf; Anthocarp; Trichomes; Kranz anatomy; Light microscopy. DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9297 Bangladesh J. Plant Taxon. 18(2): 105-115, 2011 (December)